Asas Iktikad Baik Dalam Pencegahan Dan Penyelesaian Tindakan Penyerobotan Nama Domain (Cybersquatting) Di Indonesia - Jedi Aleksander; Emilda Kuspraningrum; Febri Noor Hediati (Law Department, University of Widya Gama Mahakam Samarinda, 2025)
Background: Every person has the right to own a domain name based on the principle of first come first served registration. However, cybersquatting occurs when domain names are registered earlier using registered trademarks or other well-known names, causing harm and violating the rights of others. Cybersquatting poses legal issues because perpetrators exploit weaknesses or gaps in the first-come, first-served principle, which does not involve substantive examination. The principle of good faith plays an important role in protecting those harmed by domain name registrations under the law, especially considering that Indonesian legislation has not yet specifically regulated cybersquatting. Research Metodes: This research employs a doctrinal research method, which involves examining legal principles, norms, doctrines, and relevant statutory provisions, both from primary and secondary legal sources, to answer the research questions raised in the study. Findings: This research shows that, besides the Law on Information and Electronic Transactions, the principle of good faith in the context of domain names is also found in several other regulations, namely the Trademark Law, Uniform Domain Name Dispute Resolution Policy (UDRP), and PANDI Policy. Referring to these regulations, the principle of good faith has specific forms and limitations that can serve as benchmarks to assess whether the process of registering and using a domain name violates good faith, where violations of this principle may be indicated as acts of cybersquatting. Good faith can be used as a legal protection instrument to prevent and resolve cybersquatting, even though there is no specific regulation regarding cybersquatting in Indonesia. However, prevention still needs improvement because the domain name registration system lacks substantive examination related to trademarks, thus leaving opportunities for domain registrations that potentially infringe on the trademark rights of others. Conclusion: There is a need to establish a stricter examination mechanism within the domain name registration system to prevent cybersquatting from occurring at the initial stage of registration. Given the strong correlation between domain names and trademarks, the absence of a trademark-linked examination process allows the registration of domain names that may potentially conflict with the trademark rights of other parties. This measure would also serve to strengthen the authority of registrars and registries to reject domain name applications that do not meet the requirements of good faith, thereby helping to prevent acts of cybersquatting.